2018
DOI: 10.1016/j.jid.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil Treatment of Systemic Sclerosis Reduces Myeloid Cell Numbers and Attenuates the Inflammatory Gene Signature in Skin

Abstract: Fewer than half of patients with systemic sclerosis demonstrate modified Rodnan skin score improvement during mycophenolate mofetil (MMF) treatment. To understand the molecular basis for this observation, we extended our prior studies and characterized molecular and cellular changes in skin biopsies from subjects with systemic sclerosis treated with MMF. Eleven subjects completed ≥24 months of MMF therapy. Two distinct skin gene expression trajectories were observed across six of these subjects. Three of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 28 publications
(44 reference statements)
4
45
1
Order By: Relevance
“…High level of the myeloid cell chemo-attractant CCL2 has been found in the skin of SSc patients with the inflammatory subset and both CCL2 mRNA and CCL2 serum levels decreased during treatment with MMF. Finally, the same study confirmed the role of macrophages [25] and myeloid dendritic cells (mDC) in SSc pathogenesis, as their level seems to decrease during MMF treatment and correlate with inflammatory NES [13]. The use of belimumab and MMF for the treatment of SSc also showed similar results [26], although, authors did not show significant differences in mRSS improvement between patients treated with belimumab compared with placebo.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…High level of the myeloid cell chemo-attractant CCL2 has been found in the skin of SSc patients with the inflammatory subset and both CCL2 mRNA and CCL2 serum levels decreased during treatment with MMF. Finally, the same study confirmed the role of macrophages [25] and myeloid dendritic cells (mDC) in SSc pathogenesis, as their level seems to decrease during MMF treatment and correlate with inflammatory NES [13]. The use of belimumab and MMF for the treatment of SSc also showed similar results [26], although, authors did not show significant differences in mRSS improvement between patients treated with belimumab compared with placebo.…”
mentioning
confidence: 54%
“…It is also suggested that racial differences can be associated with distinct subsets [11]. However, patients within the same subset may show substantial different disease evolution including organ involvement as well as a heterogeneous response to treatment [12,13]. The current ACR/EULAR classification for SSc which was proposed in 2013 has significantly higher sensitivity and specificity compared with existing classification criteria [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serum anti-topoisomerase I, anticentromere, and anti-RNA polymerase III antibody titers were measured by indirect immunofluorescence at Specialty Laboratories, Valencia, CA. Healthy control participants were recruited from the Northwestern University clinical and research communities to match the age (within 10 years), race and sex of an SSc patient as previously described [11,17,18].…”
Section: Participant Recruitment and Inclusion Criteriamentioning
confidence: 99%
“…For example, DNNs perform on par with dermatopathologist review of stained skin lesion sections for diagnosis of nodular basal cell carcinomas, dermal nevi, and seborrheic keratoses [14]. In this study, we applied DNN algorithms to stained sections of skin biopsies from patients with SSc and from healthy participants [17,18]. Our goal was to test the hypothesis that DNN algorithms are sensitive to histological variation in skin biopsies and to assess the association with markers of SSc disease severity including the mRSS and two SSc gene expression biomarkers: the SSc four-gene biomarker [9] and the 4S gene expression biomarker [11].…”
Section: Introductionmentioning
confidence: 99%